Macrophage Polarization in the Skin Lesion Caused by Neotropical Species of Leishmania sp - Sandoval Pacheco, Carmen M.; Araujo Flores, Gabriela V.; Gonzalez, Kadir; De Castro Gomes, Claudia M.; Passero, Luiz F. D. [UNESP]; Tomokane, Thaise Y.; Sosa-Ochoa, Wilfredo; Zúniga, Concepción; Calzada, Jose; Saldaña, Azael; Corbett, Carlos E. P.; Silveira, Fernando T.; et al. (Hindawi, 2021)
Macrophages play important roles in the innate and acquired immune responses against Leishmania parasites. Depending on the subset and activation status, macrophages may eliminate intracellular parasites; however, these host cells also can offer a safe environment for Leishmania replication. In this sense, the fate of the parasite may be influenced by the phenotype of the infected macrophage, linked to the subtype of classically activated (M1) or alternatively activated (M2) macrophages. In the present study, M1 and M2 macrophage subsets were analyzed by double-staining immunohistochemistry in skin biopsies from patients with American cutaneous leishmaniasis (ACL) caused by L. (L.) amazonensis, L. (V.) braziliensis, L. (V.) panamensis,and L. (L.) infantum chagasi. High number of M1 macrophages was detected in nonulcerated cutaneous leishmaniasis (NUCL) caused by L. (L.) infantum chagasi (M1=112±12, M2=43±12 cells/mm2). On the other side, high density of M2 macrophages was observed in the skin lesions of patients with anergic diffuse cutaneous leishmaniasis (ADCL) (M1=195±25, M2=616±114), followed by cases of localized cutaneous leishmaniasis (LCL) caused by L. (L.) amazonensis (M1=97±24, M2=219±29), L. (V.) panamensis (M1=71±14, M2=164±14), and L. (V.) braziliensis (M1=50±13, M2=53±10); however, low density of M2 macrophages was observed in NUCL. The data presented herein show the polarization of macrophages in skin lesions caused by different Leishmania species that may be related with the outcome of the disease.